Internet connectivity disruption in Qatar (Qatar) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Qatar. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: QA-2026-0033. Severity: critical. Confidence: 67%